Análise econômica da adubação nitrogenada em feijoeiro de inverno sob plantio direto - Sabundjian, Michelle Traete [UNESP]; Arf, Orivaldo [UNESP]; Tarsitano, Maria Aparecida Anselmo [UNESP]; Kaneko, Flávio Hiroshi [UNESP]; Chaves Corsini, Daiene Camila Dias [UNESP] (My University, 2014)
With the expansion and diversity of the no-tillage system, it is necessary to evaluate the economic benefits generated throughout the production cycle, especially those related to remnants of previous crops and nitrogen fertilizer management of succeeding crops. This study aimed to evaluate the economic viability of four cover nitrogen doses on winter bean grain yield grown under no-tillage system after different crops. The experimental design was randomized blocks with four replications, in a 8x4 factorial scheme, with 32 treatments consisting of a combination of crop remnants (mayze; mayze - Azospirillum brasilense; Urochloa ruziziensis; Urochloa ruziziensis - Azospirillum brasilense; mayze + U. ruziziensis; mayze - A. brasilense+ U. ruziziensis; mayze + U. ruziziensis - A. brasilense; mayze - A. brasilense+ U. ruziziensis - A. brasilense) and cover nitrogen doses (0 kg ha-1, 30 kg ha-1, 60 kg ha-1 and 90 kg ha-1). It was possible to conclude that the highest grain yield of winter bean plants irrigated by aspersion was obtained with the use of 90 kg ha-1 of cover nitrogen in succession to Urochloa ruziziensiswithout the inoculation of Azospirillum brasilense. In order to improve profits, it is recommended to apply 90 kg ha-1 of cover nitrogen to bean crops succeeding the other crops, except for inoculated Urochloa ruziziensis.
Economic analysis of nitrogen fertilization in winter bean plant under no-tillage system
Keywords: Azospirillum brasilense; Brazilian Savannah; Phaseolus vulgaris L